Methods of Employees Payments – Empirical Research Results - Henryk Król; Iwona Rafaląt (Contemporary Economics)
In this announcement, the empirical research results of methods of employees payments are presented. The research was made in 232 Polish organizations, mainly in the limited companies. Empirical test included the middle industry companies, which realized their economic activities on the international markets. The research applied on amount of payments, their flexibility, basic and others factors of payment.